Investigation of Formazan of Benzaldehyde Compound as Corrosion Inhibitor for Preventing Mild Steel Material in Acidic Medium - Anand, B.; Balasubramanian, V. (Asian Journal of Chemistry, 2011)
Formazan of benzaldehyde has been prepared as a corrosion inhibitor to control the rate of corrosion. This compound has been investigated as corrosion inhibitor at room temperature for preventing mild steel corrosion in sulphuric acid and hydrochloric acid medium by weight loss method and electrochemical methods. The result showed that the corrosion inhibition efficiency of these compounds was found to vary with different acid concentration. It was also found that the corrosion inhibition behaviour of formazan of benzaldehyde is more in 2 N H2SO4 and 2 N HCl. So formazan of benzaldehyde can be used as a good inhibitor for preventing mild steel material in the construction of ship.